2016
DOI: 10.1093/astrogeo/atw148
|View full text |Cite
|
Sign up to set email alerts
|

The earthquake deformation cycle

Abstract: Abstract/Intro Paragraph.Earthquakes seem impossible to predict, yet they are associated with the slow deformation of tectonic plates. In the 2015 Bullerwell lecture, Tim Wright reviews observations of time-dependent surface deformation in fault zones, and uses these observations to place constraints on feasible models of the earthquake deformation cycle. The results have implications for the mechanics of fault zones and the strength of the continental lithosphere, and are critical if we are to use short-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 47 publications
2
16
0
2
Order By: Relevance
“…Theoretically speaking, with a long time series, it is possible to robustly estimate the motion of the reference point by comparing the interferometric deformation rates with the rates estimated from group delays, using co-registration shifts or the PS positions [36,37]. Moreover, if T obs is large enough, the residual atmospheric effects are also sufficiently small to fulfill even the strict requirements [8] set by applications aimed at measuring tectonic movements [5]. Notwithstanding, if T obs is not large enough to fulfill the accuracy requirements at large distances, then merging with GNSS is necessary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Theoretically speaking, with a long time series, it is possible to robustly estimate the motion of the reference point by comparing the interferometric deformation rates with the rates estimated from group delays, using co-registration shifts or the PS positions [36,37]. Moreover, if T obs is large enough, the residual atmospheric effects are also sufficiently small to fulfill even the strict requirements [8] set by applications aimed at measuring tectonic movements [5]. Notwithstanding, if T obs is not large enough to fulfill the accuracy requirements at large distances, then merging with GNSS is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Applications related to the measurement of tectonic movements are the most challenging for InSAR. The requirement of an accuracy of 1 mm/y at more that 100 km (<10 nstrain) pushes the technique to its limits [5]. Notwithstanding, it has been demonstrated that, since actual SAR missions are characterized by very stable oscillators [31] and very good orbit knowledge [32,33], such numbers can be considered achievable.…”
Section: North Anatolian Fault Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…Extrapolating a geodetic record of 2 or 3 decades to draw conclusions about an earthquake cycle likely to be several orders of magnitude greater in duration is a long‐standing challenge in earthquake hazard evaluations (Meade et al, ). Similarly, GPS measurements used in modeling long‐term lithosphere behavior are typically restricted to interseismic elastic strain, occurring at an unknown time interval after the last co‐seismic permanent strain produced by a ground rupturing earthquake (Wright, ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, under the hypothesis that earthquakes occur where strain energy has accumulated, space geodesy techniques can give such a contribution if they are able to reliably estimate the accumulation of strain, and if proper geophysical models are established that relate short-term strain estimation to long-term fault activity (Wright, 2016), complementing the spaceand time-dependent information provided by seismic flow monitoring, e.g. the pilot project in Italy, Panza et al (2011) and allowing the identification of critical seismogenic areas.…”
Section: The Case Of Amatrice Earthquakementioning
confidence: 99%